The politics of renaming "colonial" streets in Francistown, Botswana (Historia, 2021)
Francistown is located in the North East district (part of the former Tati district) in Botswana. It was "founded" in 1897 by Daniel Francis, an English prospector and the first director of the Tati Concessions (today called the Tati Company). The Tati Concessions administered the Tati district like a colony within a protectorate after annexing and effectively colonising it in the 1880s. It was not until 1969 that the company eased its total control over Francistown owing to pressure from the pan-Africanist Botswana People's Party formed in 1960. A former settler city, Francistown's street names replicate a typical European city. Since 2008, there has been pressure, mainly from councillors in the Francistown City Council, to change the city's name, rename colonial streets and some public buildings after local "heroes and heroines". In February 2011, the city's full council finally passed a motion to rename colonial streets. The proposed names are of politicians (some departed, others still alive). The initiative has not yet been executed, but the discussions and the so-called consultations are ongoing. The article examines and situates this initiative within a historical and political context, showing how politicians are manipulating this "noble" initiative by using their power and authority.  Francistown is in die Noordoos-distrik geleë (deel van die eertydse Tati-distrik) in Botswana. Dit is in 1897 deur Daniel Francis, 'n Engelse prospekteerder en die eerste direkteur van die Tati Concessions (tans bekend as die Tati Maatskappy). Die Tati Concessions het die Tati-distrik soos 'n kolonie binne 'n protektoraat bestuur nadat dit die distrik in die 1880's geannekseer en prakties gekoloniseer het. Dit was nie voor 1969 dat die maatskappy sy algehele beheer oor Francistown verslap het weens druk van die pan-Africanist Botswana People's Party wat in 1960 tot stand gebring is nie. Synde 'n voormalige setlaar-stad, het Francistown se straatname 'n tipiese Europese stad nageboots. Sedert 2008 is druk, hoofsaaklik van die kant van raadslede in die Francistown Stadsraad, uitgeoefen om die stad se naam te verander, name van koloniale strate te verander en sommige openbare geboue na plaaslike "helde en heldinne" te vernoem. In Februarie 2011 het die stad se hele raad uiteindelik 'n mosie aanvaar om koloniale straatname te verander. Die voorgestelde name is dié van politici (sommige wat reeds oorlede is, ander wat nog lewe). Die inisiatief is nog nie ten uitvoer gebring nie, maar die besprekings en die sogenaamde konsultasies word nog voortgesit. Die artikel ondersoek en plaas hierdie inisiatief binne 'n historiese en politieke konteks en toon aan hoe politici hierdie "edel" inisiatief manipuleer deur hul mag en gesag uit te oefen.
Keywords: Francistown; Street naming; Identiteitspolitiek; Daniel Francis; Straatbenaming; Politics of identity; Botswana